การศึกษาการนำหลักธรรมทางพุทธศาสนาไปใช้ในชีวิตประจำวันของนักเรียนเตรียมทหาร - พิสมัย กนกรัตน์; อิศรางกูร ณ อยุธยา วลัย (An Online Journal of Education, 2015)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาการนำหลักธรรมทางพระพุทธศาสนาไปใช้ในชีวิตประจำวันของนักเรียนทหารในประเด็นด้านการเรียน ด้านการปรับตัวและการอยู่ร่วมกันกับผู้อื่น ด้านการแก้ปัญหา และด้านการใช้จ่าย 2) ศึกษาปัจจัยในการนำหลักธรรมทางพระพุทธศาสนาของนักเรียนเตรียมทหารไปใช้ในชีวิตประจำวัน ประชากร คือ นักเรียนเตรียมทหารชั้นปีที่ 3 ประจำปีการศึกษา 2557 ที่นับถือศาสนาพุทธ จำนวน 580 นาย เครื่องมือที่ใช้ในการวิจัย คือ แบบสอบถามและแบบสัมภาษณ์ โดยนำข้อมูลจากแบบสอบถามมาวิเคราะห์หาค่าร้อยละ ค่ามัชฌิมเลขคณิต และค่าเบี่ยงเบนมาตรฐาน และนำข้อมูลจากแบบสัมภาษณ์มาวิเคราะห์ข้อมูลโดยการวิเคราะห์เนื้อหา ผลของการวิจัยพบว่า 1.นักเรียนเตรียมทหารนำหลักธรรมพระพุทธศาสนาไปปฏิบัติมากทั้ง 4 ด้าน คือ ด้านการเรียน ด้านการปรับตัวและการอยู่ร่วมกับผู้อื่น ด้านการแก้ปัญหา และด้านใช้จ่าย 2.ปัจจัยที่ทำให้นักเรียนเตรียมทหารนำหลักธรรมไปใช้ในชีวิตประจำวันไปปฏิบัติมากที่สุดคือ ต้องการมีอนาคตที่ดีและประสบความสำเร็จในหน้าที่การงาน ต้องการอยู่ร่วมกันกับผู้อื่นได้และมีมนุษยสัมพันธ์กับผู้อื่น ต้องการมีเหตุผลในการแก้ปัญหาและต้องการมีวิธีการวางแผนการใช้จ่าย และปัจจัยที่ทำให้นักเรียนเตรียมทหารนำหลักธรรมไปใช้ในชีวิตประจำวันไปปฏิบัติค่อนข้างน้อยคือ เหนื่อยล้าต่อการเรียนไม่มีสมาธิ มีโลกส่วนตัวสูงและเป็นคนเก็บตัว แก้ปัญหาตามความรู้สึกไม่มีแบบแผนในการแก้ปัญหาและมีความต้องการอยากได้สิ่งของมากกว่าการใช้ประโยชน์และแนวทางของผู้ที่นำไปใช้มากในอนาคตคือยังคงใช้หลักธรรมในการดำเนินชีวิตและส่วนผู้ที่นำไปใช้ค่อนข้างน้อยจะนำหลักธรรมไปใช้มากยิ่งขึ้น The purposes of this research were to study, 1) the application of Dhamma principles in daily life in the aspect of studying, adaptation and living with others, problem-solving and money spending. 2) factors of Dhamma principles-application in daily life of pre-cadets. The subject was 580 third year pre-cadets in academic year 2014 who were Buddhists. The research instruments were a set of questionnaires and an interview form. The data from the questionnaires were analyzed by percentage, mean and standard deviation and the data from the interview were analyzed by content analyzes . The results of the study were as follows: 1) The Pre-cadets very much applied of Dhamma principles in all aspects: studying, adaptation and living with others, and money spending 2) Factors that influence Pre-cadets who mostly applied of Dhamma principles were the desire to succeed in the future career path, the desire of living with others well and good relations with others, being rational to solve problems and the desire of having planning in the expenditure. And factors that influenced the Pre-cadets who less applied of the Dhamma principles were the fatigue of studying, being unconcentrated, being isolated person, solving problems based on feelin, no planning in solving problems and the desire of possession of materials rather than considering its usefulness. The Pre-cadets who mostly applied the Dhamma principles will continued using them in their future living and Dhamma principles will be more used among those who less applied of Dhamma principles.